Maillard reaction in Chinese household-prepared stewed pork balls with brown sauce: potentially risky and volatile products - He Li; Xiangyi Tang; Chunjian Wu; Shujuan Yu (Food Science and Human Wellness)
The stewed pork balls with brown sauce (SPB-BS) in China is well known for its delicacy and preferred by consumers. Maillard reaction (MR) is widespread in SPB-BS due to the use of sugar, meat and sauce in the thermal process. However, there is a lack of research on its risk and flavor by MR. By solid phase extraction combined with HPLC-MS, 4 kinds of harmful compounds including acrylamide (AA), heterocyclic aromatic amines (HAAs), 4-methylimidazole (4-MEI) and furan were analyzed in SPB-BS and their amounts ranged 0.05–0.50 mg/kg. The quantitative formula was proposed to evaluate the risk value of the SPB-BS, after taking into account the content, acceptable daily intake (ADI) and carcinogenicity of each compound. The risk values were in range of 0.57–37.93, suggesting that the risk caused by MR in SPB-BS was low. By head space-solid phase microextraction combined with GC-MS, 57 volatile compounds in SPB-BS were identified with the dominant contribution of alcohols, aldehydes, acids and esters. Based on the structures of these compounds and the composition of SPB-BS, lipid oxidation and MR are inferred to be responsible for the formation of the harmful and volatile compounds. In addition, the added sauces and oil provides the main precursors to form the harmful and volatile compounds in SPB-BS, so it is necessary to point out a balance between them in the further study.